La presencia del médico legista en el lugar de los hechos - Aguirre Ríos, Samanta Michelle (2021)
The proposed thesis arises due to the need to reform the comprehensive organic penal code to guarantee legal security that protects the Ecuadorian people, the presence of the legal doctor at the scene is highly relevant because his role at the crime scene is to decipher the riddle that the criminal has left. An analysis of article 461 of the comprehensive organic penal code was carried out, which allowed determining that the intervention of the legal doctor at the scene of the events is indeed necessary and that the prosecutor has the duty of monitoring what the work team that comes to the crime scene. The aforementioned law establishes that the person who must carry out the removal of the body is the prosecutor, the presence of the legal doctor is not mentioned, causing serious consequences when applying the law.